Designing Accessible Election Voting Booths: An Integrated Approach Using Universal Design, Design Thinking, and Ergonomics - Sokhibi, Akh; Cahyo Wibowo , Budi; Rachmawati, Putri; Alfarisi, Salman (Spektrum Industri, 2026)
Voting booths are one of the mandatory facilities for holding elections. However, currently, voting booths still face access barriers for people with disabilities who use wheelchairs. There is no standardization of voting booths that are easily accessible for all users and this is an urgent need for voting booth designs that are easily accessible for all users. Therefore, this study aims to design accessible voting booths for all users of voting rights. The method used in this study combines universal design approaches, design thinking, and ergonomics. Data collected included anthropometric data for people with disabilities who use wheelchairs, user need data for universal design-based voting booth designs, and user experience interview data for the empathy stage in design thinking. Data analysis used normality tests, uniformity tests, and adequacy tests for anthropometric data. On user need data, descriptive tests, level categorization and qualitative interpretation were conducted. Then, design thinking stages were carried out until design evaluation. The results of the study obtained an accessible voting booth design with dimensions of 70 cm leg room height; 75.5 cm lower table layer height; 93.2 cm upper table layer height; 92.9 table length; 55 cm table width and 55 cm booth cover height. The contribution of the study is expected to be an accessible voting booth design based on universal design, design thinking and ergonomics to become a technical guideline for the Indonesian general election commission to accommodate voter rights without discrimination.